(untitled) (Journal of Manmohan Memorial Institute of Health Sciences, 2021)
Background: Tubercular Tenosynovitis is a very rare disease and even rare to involve extensor tendons. The clinical picture is typical and confirmation is done by histopathology. Case Presentation: We present a rare case of soft tissue swelling at dorsum of wrist and distal forearm since six months. On Ultrasonogram, there were multiloculated cystic collections surrounding the extensor tendons. Lab parameters showed increased ESR and Mantoux test was positive. With the provisional diagnosis of Tenosynovitis, debulking tenosynovectomy was done where melon seed bodies were seen. Histopathology confirmed granulomatous lesions with caseous necrosis and Acid Fast Bacilli stain was also positive for the biopsy tissue. He responded to our anti-tubercular drugs with full range of motion after two months of surgery and no recurrence of swelling at four year follow up. Conclusion: Typical clinical picture, intra operative findings of melon seed bodies and rice bodies and histopathological confirmation of granulomatous lesions with caseous necrosis are pathognomonic of Tubercular Tenosynovitis. Complete debulking and antitubercular drugs cure the disease and prevents recurrence.